2018
DOI: 10.1016/j.bbabio.2017.12.003
|View full text |Cite|
|
Sign up to set email alerts
|

Complex II phosphorylation is triggered by unbalanced redox homeostasis in cells lacking complex III

Abstract: A marked stimulation of complex II enzymatic activity was detected in cybrids bearing a homoplasmic MTCYB microdeletion causing disruption of both the activity and the assembly of complex III, but not in cybrids harbouring another MTCYB mutation affecting only the complex III activity. Moreover, complex II stimulation was associated with SDHA subunit tyrosine phosphorylation. Despite the lack of detectable hydrogen peroxide production, up-regulation of the levels of mitochondrial antioxidant defenses revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Furthermore, the CIV assembly was also defective because some CIV subunits were recruited within the accumulated CIII subassemblies. A similar analysis was carried out by Páleníková et al (2021) [119], in cells bearing a 18-bp frame deletion in MTCYB gene that produced a protein shortened of six amino acids and induced a strong defect of CIII 2 activity/assembly as well as of CI and CIV [113,120,121]. These cells, differently from those with the 4-bp deletion, exhibited some amount of isolated CIII 2 and CI, that were associated in the enzymatically active CI+III 2 SC [113,121], in agreement with structural data demonstrating the existence of multiple interactions between the two complexes [74].…”
Section: Scs Biogenesis and Role Of CIIImentioning
confidence: 69%
“…Furthermore, the CIV assembly was also defective because some CIV subunits were recruited within the accumulated CIII subassemblies. A similar analysis was carried out by Páleníková et al (2021) [119], in cells bearing a 18-bp frame deletion in MTCYB gene that produced a protein shortened of six amino acids and induced a strong defect of CIII 2 activity/assembly as well as of CI and CIV [113,120,121]. These cells, differently from those with the 4-bp deletion, exhibited some amount of isolated CIII 2 and CI, that were associated in the enzymatically active CI+III 2 SC [113,121], in agreement with structural data demonstrating the existence of multiple interactions between the two complexes [74].…”
Section: Scs Biogenesis and Role Of CIIImentioning
confidence: 69%
“…Furthermore, the sign of the current changes measured can also give information on the amount of redox active molecules present out of mitochondria in different cell types. More specifically, this method allows us to clearly demonstrate that mitochondria bearing the cytochrome b microdeletion indeed produces enhanced H 2 O 2 , being this finding previously supported by indirect evidences only. In view of the relatively low amount of cells required for each measurement and considering that the bioenergetics and redox homeostasis of mitochondria play a relevant role in many physiological and pathological conditions of human biology, in the author views this approach will be of widespread interest for numerous biomedical investigations.…”
Section: Figurementioning
confidence: 79%
“…Enhanced generation of mitochondrial ROS has been associated with various diseases, in particular those caused by mutations in the mitochondrial DNA (mtDNA) affecting subunits of respiratory complexes. The RJ206 and the Δcytb cell lines are transmitochondrial hybrid cells (cybrids) exhibiting perturbations of redox homeostasis as a consequence of specific defects in respiratory complexes I (CI) and III (CIII) ,. The Δcytb cell line bears a 18‐base pair long in‐frame microdeletion in the mitochondrial MT‐CYB gene, which was identified in a patient suffering a severe encephalomyopathy and leads to the loss of six amino acid (I300‐P305) residues in the sixth transmembrane helix of cytochrome b, a subunit of CIII.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…As an oxygen sensor (Baysal et al, 2000) and key regulator of respiratory and metabolic activities, it responds to changing inflammation-linked pathologies and abnormalities (Hollinshead and Tennant, 2016, Rasheed and Tarjan, 2018, Bezawork-Geleta et al, 2018). Under harsh conditions, such as hypoxia, CII shows an increased activity, which is stimulated by reactive oxygen species (ROS) (Acín-Pérez et al, 2014, Tretter et al, 2016, Tropeano et al, 2018). Therefore, it can be concluded that CII may be the major source for the remodeling of mitochondrial energy systems in anaerobic energy metabolism (Bezawork-Geleta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%